Pemahaman Konsep Matematika Siswa Madrasah Tsanawiyah pada Statistika Ditinjau dari Gaya Belajar - Alifia Nur Haliza Putri; Sutrisno Sutrisno; Dina Prasetyowati (Arithmetic)
Understanding the concept is essential in learning mathematics, where it is possible to have different achievements based on the characteristics of students' learning styles. Therefore, this study wants to describe the ability to understand mathematical concepts in terms of students' learning styles. This qualitative research was conducted at MTs Negeri 2 Semarang. Of the 31 grade VIII students at the school, it was found that 42% had a visual learning style, 32% had an auditory learning style, and 26% had a kinesthetic learning style. Furthermore, research subjects were selected purposively based on mapping learning styles, and six students were obtained. Data collection techniques used learning style questionnaires, concept comprehension tests, and interviews. Data analysis techniques use interactive models and check the validity of the data using triangulation. Research data management and analysis using Nvivo software. The results showed no significant difference in conceptual understanding between subjects with visual, auditory, and kinesthetic learning styles. The six subjects can do the test correctly and have been confirmed through interviews. However, the two visual learning style subjects cannot show the location of the mean, median, and mode of data presented in the diagram. This finding suggests that teachers should emphasize using various mathematical representations in student learning.